Study of Residual Soil Permeability Coefficient Post Addition of Coal Fly Ash - Tarigan, Rasdinanta; Parman; Harahap, Muhammad Ari Subhan (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Residual soil is soil that is often used as barrier cover soil at the closure of B3 waste storage facilities. This is because the shear strength of the soil is quite good. The minimum value of the soil permeability coefficient (k) for barrier hoods at the closure of B3 waste storage facilities is 10-7 cm/sec. Many residual soils have a soil permeability coefficient (k) of less than 10-7 cm/sec. Because the dominant compound in coal fly ash is silica, mixing this fly ash with residual soil can reduce the value of the soil permeability coefficient (k) and is also expected to increase the shear strength value of the soil. In this study, residual soil samples were mixed with fly ash at 5%, 10%, 15%, 25% and 35% of the dry weight of the soil. This research aims to determine the effect of adding fly ash on the parameters of dry density, shear strength and soil permeability. The tests carried out were standard proctor testing, direct shear test, and Falling-Head permeability testing. The residual soil used in this research came from Hamlet I, Bintang Meriah Village, Pancur Batu District, Deli Serdang Regency. Based on standard proctor testing, the maximum density (gd max) of original soil is 1,410 gr/cm3. The largest maximum density (gd max) was obtained when adding  15% fly ash, namely 1.471 gr/cm3. In the direct shear test, the original soil cohesion value was 0.024 kg/cm² with an internal shear angle of 37.96º. In the variation of adding 15% fly ash, the cohesion value was 0.131 kg/cm² with an internal friction angle of 53.08º. Based on the Falling-Head permeability test, the original soil permeability coefficient value was 1.98 x 10-6 cm/s. The permeability coefficient value for variations in adding 15% fly ash was obtained at 8.02 x 10-8 cm/s.